Analyses of Landing Mechanics in Division I Athletes Using the Landing Error Scoring System. (March 2016) - James, Joan; Ambegaonkar, Jatin P.; Caswell, Shane V.; Onate, James; Cortes, Nelson
Background: Injury to the anterior cruciate ligament (ACL) can be detrimental to any athlete, having both short- and long-term health consequences. Examining preseason screening landing mechanics can indicate the likelihood of injury during the season. Furthermore, previous injury is also commonly referred as a predisposing factor for reinjury. Hypothesis: Players with a history of lower extremity injury would have higher Landing Error Scoring System (LESS) scores than those with no previous injury, and healthy soccer athletes who sustained an injury during the 2014 season would have higher LESS scores than those who remained uninjured. Study Design: Prospective cohort study. Level of Evidence: Level 3. Methods: Thirty-four Division I male and female soccer athletes (19 men, 15 women; mean age, 19.6 ± 1.2 years; mean height, 172.4 ± 8.7 cm; mean weight, 70.8 ± 9.1 kg). An a priori sample size estimation for a power of 0.80 (80%) and an alpha error of 0.05 with an estimated effect size of 0.6 for a sample of 30 participants was attained. Participants performed a drop-landing task and were scored on their landing mechanics using the LESS. Lower extremity injuries were tracked during the season. LESS scores between those with and without a history of injury and those who were injured and uninjured during the season were compared using 2 separate 1-way analyses of variance. Results: No statistically significant differences ( F 1, 33 = 0.47, P = 0.50) existed between LESS scores in athletes who had a previous injury history compared with those with no injury history. No statistically significant differences ( F 1, 20 = 0.05, P = 0.83) existed between LESS scores in healthy athletes who were injured during the 2014 season compared with those healthy athletes who were uninjured. Conclusion: No differences were present between athletes with and without a history of lower extremity injury. The majority of healthy participants who were injured during the season had similar LESS scores to those who remained uninjured, suggesting that the LESS may not be able to identify atypical landing mechanics in this group of athletes.